MiR-942-3p Promotes the Proliferation and Invasion of Hepatocellular Carcinoma Cells by Targeting MBL2. (2nd May 2019) - Xu, Chun-Yang; Dong, Jun-Feng; Chen, Zi-Qi; Ding, Guo-Shan; Fu, Zhi-Ren
MicroRNAs (miRNAs), a subgroup of small noncoding RNAs, play critical roles in tumor growth and metastasis. Accumulating evidence shows that the dysregulation of miRNAs is associated with the progression of hepatocellular carcinoma (HCC). However, the molecular mechanism by which miR-942-3p contributes to HCC remains undocumented. The association between miR-942-3p expression and the clinicopathological characteristics in HCC patients was analyzed by The Cancer Genome Atlas data set. The targets of miR-942-3p were identified by bioinformatic analysis and dual luciferase report assay. 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) and Transwell assays were performed to assess the functional role of miR-942-3p in HCC cells. Consequently, we found that miR-942-3p expression level was elevated in HCC tissues and cell lines as compared with the normal tissues and was associated with the pathological stage and tumor node metastasis (TNM) stage, acting as an independent prognostic factor of poor survival in patients with HCC. Ectopic expression of miR-942-3p enhanced the proliferation and invasive potential of HCC cells, but inhibition of miR-942-3p expression had the opposite effects. Mannose-binding lectin 2 (MBL2) was further identified as a direct target of miR-942-3p and possessed a negative correlation with miR-942-3p expression and unfavorable survival in patients with HCC. Restoration of MBL2 inhibited the progression of HCC cells and attenuated the tumor-promoting effects induced by miR-942-3p. In conclusion, miR-942-3p may act as an oncogenic factor in HCC cells by targeting MBL2 and provide a potential marker for patients with HCC.